Manajemen Perioperatif pada Pasien Varises Esofagus yang Menjalani Endoskopi - Sari, Djayanti; Widodo, Untung; Mi’raj, Geza Getar (Jurnal Komplikasi Anestesi, 2021)
Esophageal varices are a condition in which there is distension of the submucosal veins that project into the esophageal lumen in patients with portal hypertension. Endoscopic examination is needed in cases of esophageal variceal bleeding to confirm a diagnosis, assess varicose veins and plan their management. We report a 12-year-old patient with grade 3 esophageal varices who underwent an endoscopy procedure. Management of anesthesia in esophageal varices patients undergoing endoscopy needs to pay attention to the depth of anesthesia and to keep the patient’s airway secure to avoid hypoxemia.